Design and Construction of an Arduino Uno-Based Automatic Water Volume Dispensing System - Esron Banani; Nixson Jeheskial Meok; Tirsa Julianti Saruan; Fransiskus F. Goe Ray; Nur Hijriah Zubaedah Narang (Universitas Bandar Lampung (UBL), 2026)
This research aims to design and build an automatic dispenser with a microcontroller-based water volume metering system. The system created uses an Arduino Uno as the system control center, a YF-S401 water flow sensor to measure water volume, a solenoid valve and a water pump as a water flow regulator, and three momentary push buttons as input for selecting water volume for 150 ml, 200 ml, and 300 ml. In addition, an LED serves as an error status warning indicator when the water flow sensor fails to calculate the water volume. The research method used is the Research and Development (R&D) method which includes needs analysis, system design, hardware and software implementation, and tool performance testing. Test results show that the device is capable of measuring water with an accuracy of 93.3% at a volume of 150 ml, 96.6% at 200 ml, and 93.3% at 300 ml. Furthermore, the filling time is relatively consistent, with an average filling time of 9.54 seconds for 150 ml, 12.55 seconds for 200 ml, and 18.98 seconds for 300 ml, with a relatively small difference in filling time for each volume. In general, the device is able to work stably and according to the needs of automatic water volume measurement.